Knocking Down the Expression of GMPase Gene OsVTC1-1 Decreases Salt Tolerance of Rice at Seedling and Reproductive Stages. - Hua Qin (PLoS ONE, 2016)
Salinity is a severe environmental stress that greatly impairs production of crops worldwide. Previous studies have shown that GMPase plays an important role in tolerance of plants to salt stress at vegetative stage. However, the function of GMPase in plant responses to salt stress at reproductive stage remains unclear. Studies have shown that heterologous expression of rice GMPase OsVTC1-1 enhanced salt tolerance of tobacco seedlings, but the native role of OsVTC1-1 in salt stress tolerance of rice is unknown. To illustrate the native function of GMPase in response of rice to salt stress, OsVTC1-1 expression was suppressed using RNAi-mediated gene silencing. Suppressing OsVTC1-1 expression obviously decreased salt tolerance of rice varieties at vegetative stage. Intriguingly, grain yield of OsVTC1-1 RNAi rice was also significantly reduced under salt stress, indicating that OsVTC1-1 plays an important role in salt tolerance of rice at both seedling and reproductive stages. OsVTC1-1 RNAi rice accumulated more ROS under salt stress, and supplying exogenous ascorbic acid restored salt tolerance of OsVTC1-1 RNAi lines, suggesting that OsVTC1-1 is involved in salt tolerance of rice through the biosynthesis regulation of ascorbic acid. Altogether, results of present study showed that rice GMPase gene OsVTC1-1 plays a critical role in salt tolerance of rice at both vegetative and reproductive stages through AsA scavenging of excess ROS.